DEWAN HISBAH DALAM KEGIATAN EKONOMI - Ridha, Sovia (Alhurriyah, 2011)
Economic activities did by people sometimes do not meet the principles of justice and fairness as syari’ah by the teachings of Islam. In these activities there are also the injustice and fraud elements, so some parties are aggrieved and persecuted. Therefore, in the Islamic economic system, there is an organization that works to provide legal protection for economic actors. Legal protection is applied to prevent or at least minimize injustice and tyranny. The organization is Al Hisbah institution, which have function as amar ma’ruf nahi mungkar to control economic activities in society. Organizers of Al Hisbah are named muhtasib, both appointed by state or voluntary.